2010
DOI: 10.1093/icesjms/fsq164
|View full text |Cite
|
Sign up to set email alerts
|

Changes between consecutive broods in the fecundity of the spider crab, Maja brachydactyla

Abstract: Verísimo, P., Bernárdez, C., González-Gurriarán, E., Freire, J., Muiño, R., and Fernández, L. 2011. Changes between consecutive broods in the fecundity of the spider crab, Maja brachydactyla. – ICES Journal of Marine Science, 68: . An analysis of the fecundity of Maja brachydactyla and the possible causes for its variability was carried out during two breeding cycles in the Ría de Arousa (Galicia, NW Spain). Based on brood samples with known weight data, subsample counts were taken of the number of eggs (125 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 33 publications
2
29
0
4
Order By: Relevance
“…Variability in batch fecundity between crabs of a similar size is common in crustaceans and can be attributed to seasonal variation (Verísimo et al. ; González‐Pisani et al. ; Hjelset et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Variability in batch fecundity between crabs of a similar size is common in crustaceans and can be attributed to seasonal variation (Verísimo et al. ; González‐Pisani et al. ; Hjelset et al.…”
Section: Discussionmentioning
confidence: 99%
“…), the number of previously extruded clutches (Mantelatto and Fransozo ; Verísimo et al. ), food availability (Annala and Bycroft ; France ; Lardies and Wehrtmann ; Bas et al. ; Verísimo et al.…”
Section: Discussionmentioning
confidence: 99%
“…A female M . brachydactyla can produce an average of 300,000 eggs per brood (Pazos et al, ; Verísimo et al, ); however, it has been concluded that use of M . brachydactyla (as well as the Mediterranean spider crab, Maja squinado ) zoeae as feed for juvenile octopus production was not viable because of the need to maintain a large number of M .…”
Section: Introductionmentioning
confidence: 99%
“…), displays high fecundity (Verisimo et al . ), is able to produce multiple clutches of embryos per breeding season (Gonzalez‐Gurriaran et al . ) and exhibits a short period of embryonic development (Iglesias et al .…”
Section: Introductionmentioning
confidence: 99%